Penerapan ISAK 35 tentang Laporan Keuangan Organisasi Non-Laba pada Gereja HKI Tigabolon - Siahaan, Lassio; Purba, Sahala (Penerbit Goodwood, 2024)
Purpose: The purpose of this research is to make a comparison of the HKI Tigabolon church's preparation of financial reports in accordance with the provisions of ISAK 35. Methodology: This research uses a qualitative method with a descriptive analysis approach, comparing the theory contained in ISAK 35 with its implementation at the HKI Tigabolon Church. Data collection was carried out through observation techniques Results: The results of the research show that the Tigabolon HKI church has not undertaken its financial reporting process in accordance with current regulations, in particular ISAK 35, as its financial reports only contain information about cash receipts and expenditures. Limitation: This research focuses only on one church. Contribution: This research can encourage non-profit institutions, especially the HKI Tigabolon Church, to fully implement the current accounting standards, namely the comprehensive ISAK 35, to prepare appropriate financial reports.